GAMBARAN TINGKAT KECEMASAN SISWI KELAS VII Â DALAM MENGHADAPI PREMENSTRUASISYNDROME (PMS)DI SMPN 2 PUNGGING KABUPATEN MOJOKERTO - Santoso, Windu; Vina Agustina, Endah (JURNAL KEPERAWATAN SEHAT, 2016)
Premenstrual Syndrome (PMS), that naince of a cycle were common in the young woman and the everege, characterized by the physical symtoms emotional consistent during a phase luteal on menstrual cycle. But for young women who recently experienced it can cause anxiety, although in a different response. The anxiety problem is an important issue to be considered. The purpose of this research was to determine the level of anxiety confront VII grade SMP 2 Pungging premenstrual syndrome (PMS) in Mojokerto regency. Descriptive of the research design with a population of 102 female students of VII grade 2 Pungging. Furthermore, with purposive sampling technique samples obtained at 77students.The variabel used is the level of anxiety in female students of VII grade of premenstrual syndrome (PMS). Data were collected by questionnaire scale Hars . After processing data, followed by data analysis using frequency distribution. The results showed the majority of respondents are experiencing anxiety as many as 50 people (64,93%). It is expected that the respondents did not feel anxious with premenstrual syndrome (PMS) because it is natural and normal and common for a woman. Therefore, the respondent is expected to be morepro-active in improving the understanding of premenstrual syndrome (PMS) through a variety of sources. Health workers are expected every month regular school visits schools to provide education on health issues, especially teenagers.Keywords: anxiety level, premenstrual syndrome (PMS)